Mathematics
Alisonberg777
24

What is the solution to -6(3-k) = 6(1+3k)

+2
(2) Answers
daffneymaxwell

k=-2 is the answer. the distributive property is used here

kittysweg234

-6(3-k) = 6(1+3k) -6 x -k is going to give you a positive number while -6 x 3 is going to be a -18. 1) Simplify your equation: -18 + 6k = 6 + 18k  2) Use SAMDEB (it is an acronym you use to find the order of operation - what you do first when you solve an equation...) subtraction, addition, multiplication, division, exponents, brackets. In this case, we have subtraction and addition - it doesn't matter which one you do first... -18 + 6k = 6 + 18k  -18 = 6 + 18k - 6k -18 = 6 + 12k -18 - 6 = 12k -24/12 = 12k/12 -2 = k 

Add answer